2023
DOI: 10.3390/md21070410
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study about the Neuroprotective Effects of DHA-Enriched Phosphatidylserine and EPA-Enriched Phosphatidylserine against Oxidative Damage in Primary Hippocampal Neurons

Abstract: Nerve damage caused by accumulated oxidative stress is one of the characteristics and main mechanisms of Alzheimer’s disease (AD). Previous studies have shown that phosphatidylserine (PS) rich in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) plays a significant role in preventing and mitigating the progression of AD. However, whether DHA-PS and EPA-PS can directly protect primary hippocampal neurons against oxidative damage has not been studied. Here, the neuroprotective functions of DHA-PS and EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Nos1ap , nitric oxide synthase 1 adaptor protein, may play a role in excitotoxic neuronal damage in neurodegenerative disease ( Wang et al, 2016 ) . Atp8a1, ATPase phospholipid transporting 8A1, may be implicated in neuroprotective effects caused by pumping phosphatidylserine across the plasma membrane ( Wang et al, 2023 ). In addition, the protein encoded by the Vsnl1 gene is a calcium sensor that is known to be increased in cerebrospinal fluid in Alzheimer’s patients and may be linked to disease progression ( Liao et al, 2022 ; Zetterberg, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nos1ap , nitric oxide synthase 1 adaptor protein, may play a role in excitotoxic neuronal damage in neurodegenerative disease ( Wang et al, 2016 ) . Atp8a1, ATPase phospholipid transporting 8A1, may be implicated in neuroprotective effects caused by pumping phosphatidylserine across the plasma membrane ( Wang et al, 2023 ). In addition, the protein encoded by the Vsnl1 gene is a calcium sensor that is known to be increased in cerebrospinal fluid in Alzheimer’s patients and may be linked to disease progression ( Liao et al, 2022 ; Zetterberg, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 48 ]. A recent study in 2023 found that phosphatidylserine (PS) EPA had neuroprotective effects on primary hippocampal neurons [ 49 ]. The authors of that study found that incubation of hippocampal nerves with PS-EPA increased p-CREB (cyclic adenosine monophosphate-dependent response element-binding protein) expression by 159% ( P < 0.05), whereas PS-DHA did not have a significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this same study, synuclein expression increased to 130% after incubation with EPA-PS ( P < 0.05) but was not significantly affected after incubation with DHA-PS. Moreover, apoptosis Bcl-2 protein that acts as an inhibitor of the apoptotic pathway increased by 92% and 21% in the EPA-PS–treated and DHA-PS–treated neurons, respectively [ 49 ]. These findings emphasize the significant role of various PL-EPA species in preventing and mitigating neurodegeneration and suggest potential preventive measures for neurodegenerative diseases like AD.…”
Section: Discussionmentioning
confidence: 99%